Does induction of labor at 41 weeks (early, mid or late) improve birth outcomes in low‐risk pregnancy? A nationwide propensity score‐matched study - Anita C. J. Ravelli; Joris A. M. van derPost; Christianne J. M. deGroot; Ameen Abu‐Hanna; Martine Eskes (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Introduction This study aimed to assess whether induction of labor at 41 weeks of gestation improved perinatal outcomes in a low‐risk pregnancy compared with expectant management. Material and methods Registry‐based national cohort study in The Netherlands. The study population comprised 239 971 low‐risk singleton pregnancies from 2010 to 2019, with birth occurring from 41+0 to 42+0 weeks. We used propensity score matching to compare induction of labor in three 2‐day groups to expectant management, and further conducted separate analyses by parity. The main outcome measures were stillbirth, perinatal mortality, 5‐min Apgar <4 and <7, neonatal intensive care unit (NICU) admissions ≥24 h, and emergency cesarean section rate. Results Compared with expectant management, induction of labor at 41+0 to 41+1 weeks resulted in reduced stillbirths (adjusted odds ratio [aOR] 0.15, 95% confidence interval [CI] 0.05–0.51) in both nulliparous and multiparous women. Induction of labor increased 5‐min Apgar score <7 (aOR 1.30, 95% CI 1.09–1.55) and NICU admissions ≥24 h (aOR 2.12, 95% CI 1.53–2.92), particularly in nulliparous women, and increased the cesarean section rate (aOR 1.42, 95% CI 1.34–1.51). At 41+2–41+3 weeks, induction of labor reduced perinatal mortality (aOR 0.13, 95% CI 0.04–0.43) in both nulliparous and multiparous women. The rate of 5‐min Apgar score <7 was increased (aOR 1.26, 95% CI 1.06–1.50), reaching significance in multiparous women. The cesarean section rate increased (aOR 1.57, 95% CI 1.48–1.67) in both nulliparous and multiparous women. Induction of labor at 41+4 to 41+5 weeks reduced stillbirths (aOR 0.30, 95% CI 0.10–0.93). Induction of labor increased rates of 5‐min Apgar score <4 (aOR 1.61, 95% CI 1.01–2.56) and NICU admissions ≥24 h (aOR 1.52, 95% CI 1.08–2.13) in nulliparous women. Cesarean section rate was increased (aOR 1.47, 95% CI 1.38–1.57) in nulliparous and multiparous women. Conclusions At 41+2 to 41+3 weeks, induction of labor reduced perinatal mortality, and in all 2‐day groups at 41 weeks, it reduced stillbirths, compared with expectant management. Low 5‐min Apgar score (<7 and <4) and NICU admissions ≥24 h occurred more often with induction of labor, especially in nulliparous women. Induction of labor in all 2‐day groups coincided with elevated cesarean section rates in nulliparous and multiparous women. These findings pertaining to the choice of induction of labor vs expectant management should be discussed when counseling women at 41 weeks of gestation.